2023
DOI: 10.3390/w15132438
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Determination and Digital Geological Mapping by RS and GIS Techniques in Aseer–Jazan Contact, Southwest Saudi Arabia

Abstract: The hydrological characteristics of the watershed in the southern Aseer and northern Jazan regions of Saudi Arabia (SA) were identified by integrated remote sensing (RS) and geographic information system (GIS) techniques using Shuttle Radar Topography Mission (SRTM) and Landsat data. For this purpose, the Wadi Ishran, Wadi Baysh, Wadi Itwad, Wadi Tabab, and Wadi Bayd drainage basins were extracted. Wadi Ishran is the largest, and Wadi Tabab is the smallest. Stream order and bifurcation ratio show that the Itwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…In addition, a study conducted in southwest Saudi Arabia integrated GIS and remote sensing to determine the hydrological characteristics of a watershed in Saudi Arabia [20]. The paper's findings serve as a basis for practical applications in flood management and water harvesting [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study conducted in southwest Saudi Arabia integrated GIS and remote sensing to determine the hydrological characteristics of a watershed in Saudi Arabia [20]. The paper's findings serve as a basis for practical applications in flood management and water harvesting [20].…”
Section: Introductionmentioning
confidence: 99%
“…The study evaluated the effect of solar radiation on the basin's surface runoff, allowing them to predict the presence of saturated soil for water harvesting [19]. In addition, a study conducted in southwest Saudi Arabia integrated GIS and remote sensing to determine the hydrological characteristics of a watershed in Saudi Arabia [20]. The paper's findings serve as a basis for practical applications in flood management and water harvesting [20].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, desert regions include places where the unfertile soil is lightly unsuitable for agricultural activities and there is an undesirable climate leading to a shortage of crop and livestock products. In the context of Saudi Arabia, there has been a noticeable rise in water demand over time, specifically within the agricultural and industrial sectors [ 13 ]. Adding the existing conditions of domestic agricultural production and the resulting products will not be able to fruitfully address the increasing food demand due to the limited fertile land and water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the potential of Remote Sensing (RS) and Geographical Information Systems (GIS) for conducting morphometric analysis [25][26][27][28][29] and providing valuable information for watershed management and planning. Moreover, remote sensingbased Digital Elevation Models (DEMs) have been widely used for topography-based studies [30][31][32].…”
Section: Introductionmentioning
confidence: 99%